2016
DOI: 10.1016/j.nbd.2016.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Central HIV-1 Tat exposure elevates anxiety and fear conditioned responses of male mice concurrent with altered mu-opioid receptor-mediated G-protein activation and β-arrestin 2 activity in the forebrain

Abstract: Co-exposure to opiates and HIV/HIV proteins results in enhanced CNS morphological and behavioral deficits in HIV+ individuals and in animal models. Opiates with abuse liability, such as heroin and morphine, bind preferentially to and have pharmacological actions through μ-opioid-receptors (MORs). The mechanisms underlying opiate-HIV interactions are not understood. Exposure to the HIV-1 transactivator of transcription (Tat) protein causes neurodegenerative outcomes that parallel many aspects of the human disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 93 publications
0
31
0
Order By: Relevance
“…The analgesic properties of MOR activation are also reduced when there is an abundance of CCR5 ligands [ 80 ]. MOR function is also altered by Tat exposure, which lowers morphine efficacy through decreased G-protein activation [ 81 ]. Reduced MOR signaling would tend to increase the amounts of opiates used by HIV-infected individuals for effective analgesia or for illicit effects.…”
Section: Discussionmentioning
confidence: 99%
“…The analgesic properties of MOR activation are also reduced when there is an abundance of CCR5 ligands [ 80 ]. MOR function is also altered by Tat exposure, which lowers morphine efficacy through decreased G-protein activation [ 81 ]. Reduced MOR signaling would tend to increase the amounts of opiates used by HIV-infected individuals for effective analgesia or for illicit effects.…”
Section: Discussionmentioning
confidence: 99%
“…The iTat mouse has been utilized to investigate some of these processes. Among the many reports utilizing the iTat model just within the last decade are studies addressing Tau processing (Kadri et al 2015), host cell cycle regulation (Fields et al 2015b), cell survival (Fan and He 2016b), differentiation (Perry et al 2010; Wheeler et al 2008; Yao et al 2012) and glial activation (Kiebala et al 2010), substance abuse (Fitting et al 2012, 2010; Hauser et al 2009; Mediouni et al 2015; Paris et al 2014a; Zou et al 2011), sex differences (Hahn et al 2015a, b), behavior (Hahn et al 2016; Paris et al 2014b, c, 2015), memory and learning (Carey et al 2012; Fitting et al 2013) and brain changes observed via imaging (Carey et al 2015, 2013). Table 1, while not comprehensive by any means, provides examples of the diversity of studies that have utilized the iTat mouse model.…”
Section: Use Of Itat Mice In Studies Of Tat Neurotoxicity and Its Molmentioning
confidence: 99%
“…In the present model, Tat induction activates astrocytes (as well as bystander microglia) in the striatum ( Bruce-Keller et al, 2008 ; Fitting et al, 2010a ; Zou et al, 2011 ) and causes modest gliosis within 48 h following expression ( Bruce-Keller et al, 2008 ) that can be sustained for as long as 1 year ( Dickens et al, 2017 ). In preclinical rodent studies, CNS exposure to HIV-1 Tat induces behavioral impairments similar to HAND, including deficits in pre-attentive filter processing ( Fitting et al, 2006 ; Paris et al, 2015 ), emotionality ( Fu et al, 2011 ; Hahn et al, 2015 , 2016 ; Lawson et al, 2011 ; Paris et al, 2014 , 2016 ), motivation ( Kesby et al, 2018 ), and memory ( Carey et al, 2012 ; Fitting et al, 2013 ; Marks et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%